MINORITY RELIGIONS IN ISRAEL. Issue 1 (11th March 2015) - Sapir, Gideon; Statman, Daniel
Abstract: The article discusses the question of how Israel ought to treat its minority religions and whether its actual policies towards them accord with her moral and constitutional obligations. The first part of the paper offers three arguments purporting to show that Israel is justified in granting privileged status to the Jewish religion over other religions, and rejects each of them in turn. In particular, it rejects the view that Israel is allowed to privilege Judaism over other religions as far as the funding of religious services and needs is concerned. Nonetheless, the possibility that, on the symbolic level, weak privileging of Judaism may be permissible is left open. The second part of the paper questions whether the State of Israel guarantees equal treatment to all religions, and the answer is in the negative. Finally, the paper discusses the religious freedom of non-Jews in Israel and the way it has been interpreted by the courts. It is contended that both in terms of the freedom of religion and in terms of the freedom from religion, the protection of non-Jews is somewhat weaker than that granted to Jews, a state of affairs that ought to be remedied.